Twitter and YouTube as digital tools in higher education: a systematic review - Olivares-De la fuente, Patricia; Jiménez-García, Eva; García-López, Óscar (Frontiers in Education, 2025)
This paper presents a systematic literature review of existing studies reporting on Twitter and YouTube as digital tools in higher education. We used the PRISMA extension for scoping reviews to select articles for review and report the results. The analysis was conducted using tools such as QualSyst for quality assessment and VOSviewer for bibliometric mapping. 27 articles were selected from several databases for the final analysis on the use of YouTube and Twitter in higher education (2019–2024), highlighting their roles in communication and teaching. Key research clusters include interaction and teaching methodologies, digital video libraries, student engagement, and the role of online learning communities in enhancing collaboration and academic performance. Twitter is valued for the collaborative learning, and YouTube for summarizing and reinforcing educational content.